Luminescence modification of porous silicon decorated with GOQDs synthesized by green chemistry - Francisco Severiano Carrillo; Orlando Zaca Moran; Fernando Díaz Monge; Alejandro Rodríguez Juárez (AIMS Materials Science)
In this work, the luminescent emission control from porous silicon (PS) decorated with graphene oxide quantum dots (GOQDs) was analyzed. The samples obtained showed a 95 nm range of variation in which the luminescent emission can be controlled. Based on the results obtained from the PS samples decorated with GOQDs, the emission can be selected in a range from blue to red. Fourier transform infrared (FTIR) spectroscopy showed evidence of bond formation between PS and GOQDs. These changes can be related to the changes in luminescent emission. Photoluminescence analysis showed that the main PS emission can be selected in a 90 nm range with the introduction of GOQDs. Scanning electron microscopy (SEM) images and energy dispersive spectroscopy (EDS) spectra demonstrated the introduction of GOQDs in the PS. X-ray diffraction patterns also confirmed the presence of GOQDs on the surface of PS. In this study, different methodologies to control the luminescent emission were applied, and the results show that PS samples decorated with GOQDs showing blue, orange, and red luminescence can be obtained. The samples obtained can be applied to the development of electroluminescence devices, photodetectors, and biosensors.